Merged beam studies of mutual neutralization at subthermal collision energies. Issue 6 (January 2020) - Urbain, X.; de Ruette, N.; Dochain, A.; Launoy, T.; Nascimento, R.F.; Kaminska, M.; Stockett, M.H.; Loreau, J.; Liévin, J.; Vaeck, N.; Thomas, R.D.; Schmidt, H.T.; et al.
Abstract: We have measured the kinetic energy distributions for the mutual neutralization of a large ensemble of atomic anions and cations. Ions are accelerated to equal velocities in a merged beam setup, enabling measurements at collision energies as low as 5 meV. Three-dimensional momentum imaging is performed with two position sensitive detectors located several meters downstream from the few centimeter long region where the beams overlap. An unprecedented resolution in the kinetic energy release (KER) spectra allows us to identify the states of both reactants and products down to their fine structure. Knowing the angular distribution of the products in the laboratory and center-of-mass frame, allows for total, partial, and differential cross sections to be retrieved.